First molar extractions related to molar-incisor hypomineralization (MIH) in a special need patient: case report (Research, Society and Development, 2021)
Although most orthodontists avoid extractions, treating patients with biprotrusion traditionally involves removing teeth. In the current case report, a 15-year-old deaf patient had a Class II molar and canine relationships, 8 mm overjet and 3mm overbite, 3 mm of a discrepancy between U/L midline, crowding in both arches (3 mm in the upper and 7 mm in the lower). The first right upper molar (16) and the first right and left lower molars (36 and 46) were severely MIH affected. Extraction of the first four molars was proposed, since a large amount of space was required and three of the four molars were very compromised with severe MIH. Tooth 26 was extracted to maintain the symmetry of the arch and because the extraction of a premolar would not allow for alignment associated with class II correction of canines on the left side. During the closure of the extraction spaces, upper and lower third molars eruption was observed, in an appropriate position. Facial analysis shows us the coincidence of the upper midline with the face and good exposure of the incisors in the smile.  There was considerable reduction of overjet and dental protrusion, enabling passive lip sealing.  A perfect fit of the Class I superior teeth was not obtained since the patient considered that the treatment was already very good and did not want to collaborate with hygiene and the use of orthodontic appliances for more time.